2011
DOI: 10.1111/j.1365-2958.2011.07627.x
|View full text |Cite
|
Sign up to set email alerts
|

MecA dampens transitions to spore, biofilm exopolysaccharide and competence expression by two different mechanisms

Abstract: Summary The adapter protein MecA targets the transcription factor ComK for degradation by the ClpC/ClpP proteolytic complex, thereby negatively regulating competence in Bacillus subtilis. Here we show that MecA also decreases the frequency of transitions to the sporulation pathway as well as the expression of eps, which encodes synthesis of the biofilm matrix exopolysaccharide. We present genetic and biophysical evidence that MecA down-regulates eps expression and spore formation by directly interacting with S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 52 publications
1
41
0
Order By: Relevance
“…Furthermore, cell wall antibiotic resistance is often correlated with changes in cell wall thickness, peptidoglycan cross-linking, or decreased autolysis (10). As an adaptor protein linked with proteolysis, TrfA could conceivably contribute to the regulation of any of these steps (17,42,43). Preliminary data indeed show that trfA deletion significantly affects cell wall thickness and morphology (Renzoni, unpublished).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Furthermore, cell wall antibiotic resistance is often correlated with changes in cell wall thickness, peptidoglycan cross-linking, or decreased autolysis (10). As an adaptor protein linked with proteolysis, TrfA could conceivably contribute to the regulation of any of these steps (17,42,43). Preliminary data indeed show that trfA deletion significantly affects cell wall thickness and morphology (Renzoni, unpublished).…”
Section: Discussionmentioning
confidence: 89%
“…Study of TrfA/MecA in other organisms, notably B. subtilis, suggests that it has numerous biological functions, including as an assembly chaperone for ClpC, as an adaptor protein for regulated proteolysis of bound substrates, and as a regulator of transcription factor function (42)(43)(44)(45). Precisely how trfA contributes to drug resistance in S. aureus is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In B. subtilis, MecA was shown to be flexible in terms of interactions with different partners. For instance, it could sequester the Spo0A regulator of B. subtilis based on interactions with both domains N and C while keeping its ability to bind ComK (39). Concerning X , B2H and competitive degradation assays point toward a short region (18 aa) encompassing a predicted surface-exposed loop (F 49 to K 58 ) of its domain N as playing a preponderant role in its interaction with MecA ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…X is degraded in vitro by the MecA-ClpCP complex. Previous studies have shown that MecA of B. subtilis can either sequester a regulatory protein (i.e., Spo0A) (39) or address it to the ClpCP proteolytic machinery (i.e., ComK, ComS) (9,10). From our previous in vivo results, we have proposed that MecA not only sequesters X but is responsible for its degradation by ClpCP (31).…”
Section: Meca Interacts In Vitro With Bothmentioning
confidence: 99%
“…However, because the critical events in these processes respond with thresholds for transcription factor binding and because the basal expression of determining molecules (ComK and 0A∼P) is nonzero and noisy, the probabilities of cells embarking on development is also not zero even during exponential growth in rich media. Thus, when reporter fusions are used, cells that express comK , spoIIG (a sporulation gene), or eps are readily detected in growing cells, albeit at very low frequencies (111). In fact, small numbers of mature spores and transformable cells also form in growing cultures.…”
Section: Rare Versus Programmed Development: Meca As a Buffermentioning
confidence: 99%